2020
DOI: 10.1007/s12104-020-09950-x
|View full text |Cite
|
Sign up to set email alerts
|

Backbone resonance assignments of the catalytic and regulatory domains of Ca2+/calmodulin-dependent protein kinase 1D

Abstract: The CaMK subfamily of Ser/Thr kinases are regulated by calmodulin interactions with their C-terminal regions. They are exemplified by Ca 2+ /calmodulin dependent protein kinase 1δ which is known as CaMK1D, CaMKIδ or CKLiK. CaMK1D mediates intracellular signalling downstream of Ca 2+ influx and thereby exhibits amplifications of Ca 2+ signals and polymorphisms that have been implicated in breast cancer and diabetes. Here we report the backbone 1 H, 13 C, 15 N assignments of the 38 kDa human CaMK1D protein in it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…An integrated inflammaging model was developed to explore the important relationships among aging, inflammation and MS (shown in Section 5.3). Table 2 (Chen and D'Mello, 2010 ; Wan, 2014 ; Maridas et al, 2017 ; Jatczak-Pawlik et al, 2020 ; Tong et al, 2020 ; Black et al, 2021 ; Correale, 2021 ; Fadul et al, 2021 ; Sehgal et al, 2021 ; Atiyah et al, 2023 ) demonstrated the top ten aging, inflammatory and disease markers, respectively. For example, BMP8A (bone morphogenetic protein 8a), the top aging marker, can achieve anti-adiposity by promoting fatty acid oxidation and inhibiting adipocyte differentiation (Zhong et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated inflammaging model was developed to explore the important relationships among aging, inflammation and MS (shown in Section 5.3). Table 2 (Chen and D'Mello, 2010 ; Wan, 2014 ; Maridas et al, 2017 ; Jatczak-Pawlik et al, 2020 ; Tong et al, 2020 ; Black et al, 2021 ; Correale, 2021 ; Fadul et al, 2021 ; Sehgal et al, 2021 ; Atiyah et al, 2023 ) demonstrated the top ten aging, inflammatory and disease markers, respectively. For example, BMP8A (bone morphogenetic protein 8a), the top aging marker, can achieve anti-adiposity by promoting fatty acid oxidation and inhibiting adipocyte differentiation (Zhong et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Markov Chain Monte Carlo (MCMC) method was used to assess the sensitivity indices between inflammaging and MS. As a result, the 35 sensitive triples (by calculating the absolute difference frequency) were shown in Table 3 (Sarasin-Filipowicz et al, 2009 ; Chen and D'Mello, 2010 ; Bergbold and Lemberg, 2013 ; Liu et al, 2013 ; Malhotra et al, 2013 ; Wan, 2014 ; Charbit et al, 2015 ; Fusco et al, 2015 ; An et al, 2017 ; Arentsen et al, 2017 ; Maridas et al, 2017 ; Mathur et al, 2017 ; Xiao et al, 2019 ; Immler et al, 2020 ; Sato et al, 2020 ; Tong et al, 2020 ; Buhelt et al, 2021 ; Correale, 2021 ; Fadul et al, 2021 ; Ma et al, 2021 ; Peng et al, 2021 ; Bogacka et al, 2022 ; Franceschi et al, 2022 ; Hjæresen et al, 2022 ; Khurana and Goswami, 2022 ; Liu S. et al, 2022 ; Schebb et al, 2022 ; Watanabe et al, 2022 ; Saeidi et al, 2023 ). For example, the sensitive triple with maximum difference was “TMPRSS13-USP18-DCHS2” (the absolute difference value was 0.270469).…”
Section: Resultsmentioning
confidence: 99%